Ethnomathematic Numeralia Calculation System Dwar Subdialek Language North Biak As A Learning Media - Musa Hemer Smas; Meggy Merlin Mokay (Institute of Computer Science (IOCS), 2022)
Numeralia is a term for counting the number of forms (individuals, animals, or objects) and ideas. In the vicinity of Dwar Village, the use of Biak regional language numerals has evolved with the passage of time. Young generation Z (1990-2000) communicates only in Indonesian (B2). At contrast, generation Y (1980-1990) did not teach or practice the Biak regional language to generation Z in Dwar Village. The generation born between 1950 and 1970 still utilizes the Biak regional language in talks with their parents. The current state of Biak language use in Kampung Aman is in flux. When communicating in the Biak language, Generation Z frequently has trouble pronouncing words pertaining to numeralia or numbers. The objective of this project is to produce written documentation of the Biak regional language's numerals for the numbers 1-1000 in Biak. By providing the formula code for the number calculation system in the Biak dialect Dwar, the number will be written. Through its documentation and calculating system, generation Z and later generations can acquire Biak numerals, comprehend and use them in spoken and written language, and serve as alternative learning medium.This study employed the synchronous approach by examining the use of the Biak Subdialek Dwar regional language by generation Z over a period of 1-2 years. The study's results include documents. This study's Biak numeral data consists of five sections: (1) fundamental numbers, (2) intermediate numbers, (3) tens numbers, (4) hundreds numbers, (5) thousands numbers, and (6) a number computation system with formula codes.